DIPLOMASI BUDAYA INDONESIA - JEPANG MELALUI VIRTUAL YOUTUBER HOLOLIVE DALAM MEMPERKENALKAN BAHASA DAN BDAYA JEPANG KE INDONESIA PADA TAHUN 2019 - 2022 - Vina Mafazah, (2023)
Japan is a country that is aggressive in conducting diplomacy, especially in the field of culture. However, the popularity of Japanese language and culture declined due to the emergence of Korean language and culture which became a public concern. This has made Japan more aggressive in exploiting its country's soft power. Japan conducts diplomacy with other countries, one of which is cultural diplomacy. The Cultural Diplomacy carried out by Japan made Indonesia its target. Due to technological developments, Japan utilizes one platform, namely YouTube. This phenomenon eventually created the term Virtual Youtuber (VTuber). By using qualitative methods, this study aims to analyze VTuber Hololive as an instrument of Japanese cultural diplomacy in introducing Japanese language and culture. Based on the concept of Soft Power, VTuber can be said to be a medium for increasing popularity and the number of VTubers both in Japan and outside Japan is proof that Japanese soft power provides convenience to soft diplomacy carried out by Japan, especially in terms of language and culture. Judging by using the theory of cultural diplomacy and digital diplomacy, Japan has succeeded in making VTuber Hololive Productions to benefit from collaboration in these activities, namely one of which is Japanese language and culture, especially in Indonesia.